2018
DOI: 10.17575/rpsicol.v32i1.1333
|View full text |Cite
|
Sign up to set email alerts
|

Testing functional theory of life values with students living in residential care institutions

Abstract: The Functional Theory of Life Values can constitute a useful theoretical basis for evaluating and promoting the psychosocial development of young people. This study aimed to analyze the adequacy of this theory with students living in residential care institutions. We tested two main hypotheses: a content hypothesis, using a six-dimensional values model (excitement, promotion, existence, supra-personal, interactive, normative), and a structure hypothesis, which represents values in two space dimensions (type of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 7 publications
1
2
0
2
Order By: Relevance
“…By comparing the first three positions of the most frequently preferred values, we detected identical positioning of values honesty (1 st rang), responsibility (2 nd rang), and ambition (3 rd rank) between less experienced and the most experienced teachers, while experienced teachers positioned value responsibility in 3 rd place (Table 5). The obtained results are in accordance with the results of value research aimed at obtaining social and personal goals (Marques et al, 2018;Marischuk & Voitko, 2017;Giacomino at al., 2011;Matejević, 2008;Koković & Lazar, 2004). With values ranked lowest on the list, there is a total disagreement between all groups of teachers on the preference of self-control and helpfulness (14 th rank) and obedience (15 th rank).…”
Section: Positioning Teachers' Instrumental Values With Regard To The...supporting
confidence: 90%
“…By comparing the first three positions of the most frequently preferred values, we detected identical positioning of values honesty (1 st rang), responsibility (2 nd rang), and ambition (3 rd rank) between less experienced and the most experienced teachers, while experienced teachers positioned value responsibility in 3 rd place (Table 5). The obtained results are in accordance with the results of value research aimed at obtaining social and personal goals (Marques et al, 2018;Marischuk & Voitko, 2017;Giacomino at al., 2011;Matejević, 2008;Koković & Lazar, 2004). With values ranked lowest on the list, there is a total disagreement between all groups of teachers on the preference of self-control and helpfulness (14 th rank) and obedience (15 th rank).…”
Section: Positioning Teachers' Instrumental Values With Regard To The...supporting
confidence: 90%
“…Based on the FTLV, the basic values survey (BVS; Gouveia, 2003), was constructed. The FTLV hypotheses using the BVS have been corroborated in Brazil (Gouveia et al, 2009(Gouveia et al, , 2010(Gouveia et al, , 2014(Gouveia et al, , 2015 and confirmed in several other countries (Ardila et al, 2012;Gouveia et al, 2010;Marques, Silva, & Taveira, 2018;Marques et al, 2016;Medeiros, 2011;Mohamed et al, 2019). However, these studies were conducted mostly in European or occidental countries, with the exception of Egypt and Israel, and mostly with groups of the general population.…”
Section: Literature Review Functional Theory Of Life Valuesmentioning
confidence: 84%
“…Na základe preštudovanej literatúry sme si stanovili tri hypotézy, ktoré porovnávajú hodnoty medzi našimi výskumnými skupinami. Predpokladali sme, že prvá výskumná skupina, adolescenti z centier pre deti a rodinu budú zastávať hodnoty moc a úspech v menšej miere ako druhá výskumná skupina, adolescenti vyrastajúci v rodinách (Marques et al, 2018;Tulviste & Gutman, 2003). V našej práci sa nám tento predpoklad nepotvrdil.…”
Section: Diskusiaunclassified
“…Konformita sa okrem iného vyznačuje aj súhlasom, prispôsobením sa, nepresadzovaním svojho názoru, poslušnosťou. Pri tejto hodnote Tulviste a Gutman (2003) tvrdili, že adolescenti z CDR budú konformitu zastávať vo vyššej miere a naopak Marques et al (2018) prišli s výsledkom, že adolescenti z CDR zastávajú konformitu v nižšej miere. Náš výsledok je v zhode s výsledkami štúdie od Marquesa et al (2018), ktorí poukazujú na fakt, že inštitucionálne deti vo vyššej miere porušujú pravidlá.…”
Section: Diskusiaunclassified